2008
DOI: 10.1186/1756-0500-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of palpation-versus ultrasound-guided fine-needle aspiration biopsies in the evaluation of thyroid nodules

Abstract: BackgroundThe aim of this study was to compare the results of palpation-versus ultrasound-guided thyroid fine-needle aspiration (FNA) biopsies.FindingsClinical data, cytology and histopathology results were retrospectively analyzed on all patients who underwent thyroid FNA biopsy in our outpatient endocrinology clinic between January 1998 and April 2003. The same investigators performed all thyroid FNAs (ASC) and cytological evaluations (KP). Subjects in the ultrasound-guided group were older, otherwise there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 15 publications
(26 reference statements)
1
60
1
1
Order By: Relevance
“…The causes of inadequacy may be failure to aspirate from the proper site, cystic papillary carcinoma, technical error, variable criteria adopted for adequacy in different institutions. (16) Secondly, categorising thyroid follicular lesions into benign and malignant neoplasm is very difficult by cytology. This is unavoidable as the distinction requires demonstration of capsular and vascular invasion by histology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of inadequacy may be failure to aspirate from the proper site, cystic papillary carcinoma, technical error, variable criteria adopted for adequacy in different institutions. (16) Secondly, categorising thyroid follicular lesions into benign and malignant neoplasm is very difficult by cytology. This is unavoidable as the distinction requires demonstration of capsular and vascular invasion by histology.…”
Section: Discussionmentioning
confidence: 99%
“…13 So, we included both lesions under umbrella term follicular neoplasm, according to standard guidelines. USG examination of thyroid and neck is a basic diagnostic imaging method providing information on structure of parenchyma of thyroid gland, its relationship to its surroundings and on regional lymph nodes 16 . Modern high resolution and Doppler ultrasound has allowed the definition of suspicious features over & above description as solid or cystic and these include microcalcification, the irregularity of the nodule margin and intralesional vascularity (13) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of a cyst does not exclude neoplasia, especially if the mass is mixed. Desjardins et al found that one half of their patients with thyroid carcinoma had a cystic component in the tumor [2].…”
Section: The Relation Between Thyroid Nodules and Thyroid Malignancy mentioning
confidence: 99%
“…A prospective trial from Istanbul compared the accuracy of palpation vs US-FNA and found the inadequate rate was 27% vs 13% for the US-FNA group 51 . The usefulness of US-FNA has reached such acceptance that most published trials in the last few years use US-FNA exclusively regardless of whether nodules are solitary, multiple, palpable or impalpable.…”
Section: Ultrasound Guided Fna Vs Palpationmentioning
confidence: 99%